Viscosity of Pyroxenite Melt and Its Evolution During Cooling. Issue 5 (30th May 2019) - Vetere, F.; Murri, M.; Alvaro, M.; Domeneghetti, M. C.; Rossi, S.; Pisello, A.; Perugini, D.; Holtz, F.
Abstract: New viscosity experiments at superliquidus temperatures and during cooling at a rate of 10 K/hr have been performed at different shear rates on a synthetic pyroxenite melt. Results revealed that this melt is extremely fluid at temperature between 1646 and 1530 K and measured viscosities are between 2.2 and 7.8 Pa·s. Such very low viscosities allow the lava to flow in turbulent regime as confirmed by the high Reynolds numbers, which are always >2, 000. As a consequence, very long distance could be covered by the lava flow. If we consider this studied composition as proxy for Mars lava flows coupled with very high effusion rates, our results might explain the presence of extraordinary large volcanic channels, as recently hypothesized for the Kasei Valles on Mars, even considering that the gravity is approximately one third that of Earth. Few literature data tracking viscosity during cooling are available, and they reported shear thinning effect on different compositions. Our experiments performed at 0.1 and 1 s −1 have shown complex variation in the apparent viscosity, confirming that nonequilibrium rheology represents a still unexplored field of investigation useful to better understand the real geological scenarios occurring in magmatic and volcanic systems. Plain Language Summary: The study of the flow of matter (rheology) is the key factor to understand dynamic processes and behavior of magma rising through volcanic conduit and lava emplacement on Earth or other terrestrial planets. Today we can monitor the evolution of magma and volcanic mixtures by measuring their viscosity and its variation as temperature, composition, and fluid regimes vary. The available data are mainly derived from isothermal experimental approaches, and very few studies focused on monitoring viscosity behavior while changing both the cooling rate and the shear stress. In this study we have monitored in detail the viscosity variation of an analog composition prepared to reproduce Theo's Flow lava (Ontario, CA), considered as a terrestrial analog of Martian nakhlites. Measurements were performed using the concentric cylinder technique. Results show a very high fluidity of the melt in the temperature range between 1643 and 1530 K (2.2 to 7.8 Pa·s). As temperature drops into the subliquidus temperature (i.e., below 1530 K), apparent viscosity continuously increases to 6 × 10 4 Pa·s, where a brittle failure was observed. These results can provide indications on how extraordinary long lava flows might have developed on the Martian surface. Key Points: New viscosity data under controlled cooling and shear rates for a pyroxenite, analog of Martian nakhlites, are presented Changes in apparent viscosity behavior are observed with a decrease of viscosity of approximately 1 log unit between two different experiments as shear rate ( γ ̇ ) varies from 0.1 to 1.0 s −1 Lava flow capability and crystallization dynamics are discussed in the framework of possible scenarios occurring on Earth and on Mars